HUBUNGAN PROKRASTINASI AKADEMIK DENGAN HASIL BELAJAR IPS KELAS VIII SMP NEGERI 3 BANDUNG - Azhari Azaria Fauzi, - (2023)
As a result of the impact of COVID 19 two years ago on the education sector, academic stres on students is a long-term problem which until now has created new problems that are often experienced by students. One of these problems is academic procrastination or delayed activities that make students to avoid stress or negative feelings while doing academic activities. This academic procrastination is a bad activity that if done continuously by students, will determine academic performance or in specific, learning outcomes. This research was conducted to prove that there is a relationship between academic procrastination and learning outcomes, especially social studies learning outcomes which are considered important in helping students as social beings who are able to increase their understanding of the national spirit and community activities in the socio-economic field in the Republic of Indonesia. This study used a descriptive correlational method with 163 samples from students of 8th grade in SMP Negeri 3 Bandung using questionnaire as a tool to collect data. The correlation technique used in this study is Spearman's correlation, with the results of t count is 4.479, as well as the results of the correlation coefficient is -0.323 with a significance 0.000, also the coefficient of determination is 10.43%. The results of this study indicate that 1) there is a significant negative relationship with a weak level of relationship between procrastination and social studies learning outcomes, and 2) the effect of academic procrastination is 10.43% on learning outcomes in 8th grade students in SMP Negeri 3 Bandung.